ANALISIS SISTEM AKUNTANSI PENGELUARAN KAS PADA BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN DAERAH KOTA MANADO - Rondonuwu, Clarissa Bellinda; Ilat, Ventje; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
A good cash disbursement system in government agencies has several important benefits, among others, is to make effective the costs incurred by government agencies, prevent the occurrence of misuse, misappropriation and embezzlement of cash and help agencies in predicting the determination of the amount of cash budget that should be available for activities in the coming period. This study aims to determine the cash disbursement system based on Domestic Regulation No. 21 of 2011. The research was conducted at the Manado Regional Research and Development Planning Board. In this study the source of the data used is primary data obtained directly through interviews and the informant used was the chairman of the financial sub-section. The results obtained showed that the accounting information system regarding the cash disbursement system was good, even in its implementation it was in accordance with Domestic Regulation No. 21 of 2011